2012
DOI: 10.1111/j.1600-0587.2012.07488.x
|View full text |Cite
|
Sign up to set email alerts
|

Broad‐scale geographic patterns in body size and hind wing development of western Palaearctic carabid beetles(Coleoptera: Carabidae)

Abstract: Research into large‐scale ecological rules has a long tradition but has received increasing attention over the last two decades. Whereas environmental, especially climatic, influences on the geographic distribution of species traits such as body size are well understood in mammals and birds, our knowledge of the determinants and mechanisms which shape spatial patterns in invertebrate traits is still limited. This study analyzes macroecological patterns in two traits of the highly diverse invertebrate taxon of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 75 publications
(141 reference statements)
5
42
0
Order By: Relevance
“…, Brehm and Fiedler , Homburg et al. ). Furthermore, a recent study showed that both the phylogenetic (the legacy of the phylogenetic relationship) as well as the species‐specific component (the deviation of a species from the phylogenetic legacy) of color contribute to the pattern of increasing color lightness in butterfly and dragonfly assemblages toward warm environments across Europe (Zeuss et al.…”
Section: Introductionmentioning
confidence: 99%
“…, Brehm and Fiedler , Homburg et al. ). Furthermore, a recent study showed that both the phylogenetic (the legacy of the phylogenetic relationship) as well as the species‐specific component (the deviation of a species from the phylogenetic legacy) of color contribute to the pattern of increasing color lightness in butterfly and dragonfly assemblages toward warm environments across Europe (Zeuss et al.…”
Section: Introductionmentioning
confidence: 99%
“…These microevolutionary processes enable carabid beetles to adapt to specific habitats (cf. Thiele, ) and might even drive patterns at smaller and larger geographical scales, which have been documented (Šerić Jelaska & Durbešić, ; Homburg et al ., ).…”
Section: Content Of Carabidsorgmentioning
confidence: 97%
“…Invertebrate body size has been considered in an increasing number of macroecological studies on large geographical scales and reflects physiological abilities such as starvation and desiccation resistance (Remmert, ; Cushman et al ., ; Entling et al ., ) and energy allocation (Atkinson, ; Mousseau, ) as well as dispersal abilities (Cushman et al ., ). Broad‐scale patterns in body size distribution of western Palaearctic carabids showed increasing body size towards regions with (long‐term) stable climate conditions and high energy and water availability (Homburg et al ., ). On a more regional assemblage‐level, body size was found to be linked with habitat succession and stability (Schwerk & Szyszko, ; Šerić Jelaska et al ., ) as well as with distribution (Schwerk & Szyszko, ).…”
Section: Content Of Carabidsorgmentioning
confidence: 99%
“…Moreover, the semi‐passive or passive oxygen dissipation that is ubiquitous in insects involves a more effective respiration and cell functioning at higher temperatures, which would allow species to attain larger body sizes at higher ambient temperature and, hence, at lower latitudes (Fattorini, Lo Monaco, Giulio, & Ulrich, ). Finally, an increase in body size at lower latitudes might be due to increased productivity and metabolic rates in regions with high energy availability (Heino & Alahuhta, ; Homburg et al, ). However, studies on temperature relationships and latitudinal trends in arthropod body size have provided variable results, pointing to taxon and life history specific factors that constrain body size, such as taxon‐specific desiccation resistance, resource storage and starvation resistance, resource limitation, food availability, freezing resistance, net primary productivity, seasonality and metabolic constraints (Fattorini et al, ; Heino & Alahuhta, ).…”
Section: Introductionmentioning
confidence: 99%